Impact of Information Technology on The Performance of Tunisian Banks: A Stochastic Frontier Analysis with Panel Data - Syrine Ben Romdhane (Asian Academy of Management Journal of Accounting and Finance, 2013)
This paper investigates the performance of information technology (IT) investments in a sample of 15 Tunisian banks over the period 1998–2009. We employ the standard Stochastic Frontier Approach on panel data to generate estimates of cost efficiencies. The study is enhanced by a comparison between the results found using the Data Envelopment Analysis (DEA) method and the Stochastic Frontier Analysis (SFA) method to test the soundness of these approaches to efficiency measurement. The empirical findings suggest that the impact of IT investments on Tunisian banks’ performance is positive. The analysis of the internal determinants of banks’ efficiency levels shows that size and managerial capacity positively and significantly affect the Tunisian banks’ cost efficiency, while the share of non-performing loans represents a source of inefficiency. Measuring the impact of various categories of IT investments (hardware, software and IT services) on banks’ cost efficiencies suggests that “the Productivity Paradox” does not affect all IT investments.